Synthesis, Characterisation, DFT and Docking Analysis of 3-Methyl-2,6-bis(3-methylphenyl)piperidin-4-one (MBMP) as Anti-Retroviral Therapeutic Agent - Stuart, J. Gershom; Jebaraj, J. Winfred (Asian Journal of Chemistry, 2026)
RNA is vital in HIV gene expression and replication. Despite antiretroviral therapy (ART) advancements, the high mutation of HIV rate remains challenging. In this work, the synthesis, quantum chemical analysis and molecular docking of 3-methyl-2,6-bis(3-methyl-phenyl)piperidin-4-one (MBMP) were carried out to evaluate its potential as an anti-retroviral therapeutic agent. The synthesized MBMP was structurally confirmed through standard spectroscopic techniques and its molecular geometry along with electronic properties were further optimized using density functional theory (DFT) calculations performed with Gaussian 16W in the gas phase. The electronic structure of the optimised structure has been identified through the density functional theory (DFT) approach. All calculations were performed at the B3LYP/6-311G(d,p) level of theory and the resulting HOMO–LUMO energies were analyzed to elucidate the system’s stability, reactivity and electronic properties. The Fukui function was determined to identify reactive sites within the molecule, while Mulliken population analysis was employed to evaluate the charge distribution on individual atoms. Molecular electrostatic potential (MEP) analysis was employed to identify electron-rich and electron-deficient regions, while natural bond orbital (NBO) analysis provided insight into molecular stability. Further analyses, including non-covalent interactions (NCI), scanning tunneling microscopy (STM), aromaticity and LOL-based shaded surface maps, were carried out using Multiwfn 3.8, while UV and NMR spectroscopy validated structural integrity and purity, and binding interactions were elucidated using Discovery Studio Visualizer.